2008
DOI: 10.1029/2007jd008605
|View full text |Cite
|
Sign up to set email alerts
|

Fossil and contemporary fine particulate carbon fractions at 12 rural and urban sites in the United States

Abstract: [1] Fine particulate matter collected at two urban, four near-urban, and six remote sites throughout the United States were analyzed for total carbon (TC) and radiocarbon ( 14 C). Samples were collected at most sites for both a summer and winter season. The radiocarbon was used to partition the TC into fossil and contemporary fractions. On average, contemporary carbon composed about half of the carbon at the urban, $70-97% at near-urban, and 82-100% at remote sites. At Phoenix, Arizona, and Seattle, Washington… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
168
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(195 citation statements)
references
References 84 publications
25
168
2
Order By: Relevance
“…In the presence of anthropogenic pollutants, such as NO 2 and acidic aerosol produced from the oxidation of SO 2 , SOA mass yields from isoprene under highand low-NO x conditions, respectively, increase substantially. Because isoprene is estimated to be the largest single contributor to global SOA, these results may help to resolve two existing dilemmas in atmospheric chemistry: (i) Radiocarbon ( 14 C) data consistently indicate that well over half of the ambient SOA is of modern (biogenic) origin (7,33), whereas correlations between water-soluble organic carbon and anthropogenic tracers, such as CO, suggest that much of the SOA is actually of anthropogenic origin (34,35); and (ii) comparisons between measured and predicted SOA based on known precursors suggest that there is a substantial amount of "missing urban SOA" not included in current models (35)(36)(37). Revising the chemistry of isoprene in regional and global SOA models could lead to a decrease in this discrepancy; however, the measurement and parameterization of aerosol acidity requires additional work.…”
Section: Identification Of Mpan As Key Intermediate In Formation Of Smentioning
confidence: 99%
“…In the presence of anthropogenic pollutants, such as NO 2 and acidic aerosol produced from the oxidation of SO 2 , SOA mass yields from isoprene under highand low-NO x conditions, respectively, increase substantially. Because isoprene is estimated to be the largest single contributor to global SOA, these results may help to resolve two existing dilemmas in atmospheric chemistry: (i) Radiocarbon ( 14 C) data consistently indicate that well over half of the ambient SOA is of modern (biogenic) origin (7,33), whereas correlations between water-soluble organic carbon and anthropogenic tracers, such as CO, suggest that much of the SOA is actually of anthropogenic origin (34,35); and (ii) comparisons between measured and predicted SOA based on known precursors suggest that there is a substantial amount of "missing urban SOA" not included in current models (35)(36)(37). Revising the chemistry of isoprene in regional and global SOA models could lead to a decrease in this discrepancy; however, the measurement and parameterization of aerosol acidity requires additional work.…”
Section: Identification Of Mpan As Key Intermediate In Formation Of Smentioning
confidence: 99%
“…Joint approaches: They include approaches such as the EC-tracer method combined with radiocarbon ( 14 C) analysis [29], radiocarbon analysis with chemical mass balance (CMB) [30], and the direct estimation of SOC with input of secondary species when applying the positive matrix factorization (PMF) model [31]. Last, aerosol mass spectrometry (AMS) is an advanced approach providing high time resolution [32].…”
Section: Introductionmentioning
confidence: 99%
“…Sources of WSOC have been shown to be complex. They are emitted directly from combustion, industrial, and natural sources (primary) and/or formed through secondary processes such as homogeneous gas-phase and/or heterogeneous aerosol-phase oxidation (secondary) (Claeys et al, 2004;Koch et al, 2007;Schichtel et al, 2008). Although the primary sources such as biomass burning may be important for WSOC loadings , it is suggested that a major fraction of WSOC is from secondary organic aerosol (SOA) formation (Aggarwal and Kawamura, 2009;Kondo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%